If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (750 + -1x) + -600 + -1y = 3x + -1y Remove parenthesis around (750 + -1x) 750 + -1x + -600 + -1y = 3x + -1y Reorder the terms: 750 + -600 + -1x + -1y = 3x + -1y Combine like terms: 750 + -600 = 150 150 + -1x + -1y = 3x + -1y Add 'y' to each side of the equation. 150 + -1x + -1y + y = 3x + -1y + y Combine like terms: -1y + y = 0 150 + -1x + 0 = 3x + -1y + y 150 + -1x = 3x + -1y + y Combine like terms: -1y + y = 0 150 + -1x = 3x + 0 150 + -1x = 3x Solving 150 + -1x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 150 + -1x + -3x = 3x + -3x Combine like terms: -1x + -3x = -4x 150 + -4x = 3x + -3x Combine like terms: 3x + -3x = 0 150 + -4x = 0 Add '-150' to each side of the equation. 150 + -150 + -4x = 0 + -150 Combine like terms: 150 + -150 = 0 0 + -4x = 0 + -150 -4x = 0 + -150 Combine like terms: 0 + -150 = -150 -4x = -150 Divide each side by '-4'. x = 37.5 Simplifying x = 37.5
| 120.08=2808.97(r) | | (2y-80)=(y+9) | | 7(d-3)+6= | | (8x+12)=(10x-24) | | 3x-4+4x+8+x=180 | | (x+30)=(2x) | | 7x-4x+x-4+3x= | | 6.5x-5+x-1.2= | | 4b-6-9b-8= | | 682/d=21 | | (3x-15)=(2x+25) | | -5=5x+5y | | 50(t)=-16t^2+50o | | 50(t)=-16t^2+ho | | h(t)=-16t^2+ho | | 2(-8)-21(-8)-7= | | 25-15(-8)= | | 45=9/2h | | 25-15(8)= | | 45=1/2h(9) | | 2(8)-21(8)-7= | | ×=2/3 | | 9/7(M-19) | | -2x+3=5x-2 | | 7x^9/8-35=0 | | -7(3)+13= | | 2178=p(1+.03*7) | | 10y=72+y | | 2/3-(5/6) | | 4x+5y-28=0 | | 7x+8=5x-8 | | 2.4/0.3=x |